Aceh and the Politics of Islamic Identity: Implications for Social and Political Dynamics - Hakim, Putri Rahmah Nur; Abdullah, Irwan; Marlina, Lina (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2024)
Studying the intersection of Islamic identity politics and governance in Aceh is crucial due to its implications for regional autonomy and national cohesion. Aceh's special autonomy, allowing the enforcement of Sharia law, highlights a unique governance model within Indonesia. This issue is underexplored in current research, which often overlooks the nuanced impacts of Islamic identity politics on both local governance and national policy integration. Previous studies have primarily focused on general autonomy or Islamic law without delving into how these elements specifically interact within Aceh's political context. This study aims to bridge this gap by investigating how Islamic identity politics influences Aceh's legal and governance systems and its conflict with national policie. Using the theory of political identity and autonomy, the research employs a qualitative approach with a focus on case studies in Aceh, the research employs a qualitative approach with a focus on case studies in Aceh. The main data collection techniques used in this study include online news document analysis and direct observation. The study's findings reveal the complex dynamics between Aceh’s local Islamic values and national legislative pressures, providing new insights into regional autonomy challenges.